Auxin-mediated stress relaxation in pericycle and endoderm remodeling drives lateral root initiation - Ramos, João R. D.; Reyes Hernández, Blanca Jazmín; Alim, Karen; Maizel, Alexis (Biophysical journal, 2025)
Plant development relies on the precise coordination of cell growth, which is influenced by the mechanical constraints imposed by rigid cell walls. The hormone auxin plays a crucial role in regulating this growth by altering the mechanical properties of cell walls. During the postembryonic formation of lateral roots, pericycle cells deep within the main root are triggered by auxin to resume growth and divide to form a new root. This growth involves a complex interplay between auxin, growth, and the resolution of mechanical conflicts with the overlying endodermis. However, the exact mechanisms by which this coordination is achieved are still unknown. Here, we propose a model that integrates tissue mechanics and auxin transport, revealing a connection between the auxin-induced relaxation of mechanical stress in the pericycle and auxin signaling in the endodermis. We show that the endodermis initially limits the growth of pericycle cells, resulting in a modest initial expansion. However, the associated stress relaxation is sufficient to redirect auxin to the overlying endodermis, which then actively accommodates the growth, allowing for the subsequent development of the lateral root. Our model uncovers that increased pericycle turgor and decreased endodermal resistance license expansion of the pericycle and how the topology of the endodermis influences the formation of the new root. These findings highlight the interconnected relationship between mechanics and auxin flow during lateral root initiation, emphasizing the vital role of the endodermis in shaping root development through mechanotransduction and auxin signaling.
Gesehen am 05.09.2025